Response of ADHD with Giant SEP to Valproate - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Three boys, ages 4.5, 6, and 6.7 years, with attention deficit/hyperactivity disorder (ADHD) associated with giant somatosensory evoked potentials (SEP), who responded well to extended-release valproate (ER-VPA), are reported from the University of Tokushima Graduate, and Miyoshi Medical Clinic, Higashikagawa, Japan.